2011
DOI: 10.1128/iai.00158-11
|View full text |Cite
|
Sign up to set email alerts
|

Chitin-Induced Carbotype Conversion in Vibrio vulnificus

Abstract: As an etiological agent of bacterial sepsis and wound infections, Vibrio vulnificus is unique among the Vibrionaceae. The most intensely studied of its virulence factors is the capsular polysaccharide (CPS). Over 100 CPS types have been identified, yet little is known about the genetic mechanisms that drive such diversity. Chitin, the second-most-abundant polysaccharide in nature, is known to induce competence in Vibrio species. Here, we show that the frequency of chitin-induced transformation in V. vulnificus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 74 publications
1
24
0
Order By: Relevance
“…In V. parahaemolyticus, genes within this cluster are involved in the synthesis of capsular polysaccharides (CPS) and play a role in the formation of biofilms (Chen et al, 2010). The cps cluster is known to be highly variable, and previous work has shown that recombination within this locus can be driven by chitin-induced transformation (Neiman et al, 2011). Five CPS proteins, unique to ST36, showed significant homology to putative virulence factors described in other Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…In V. parahaemolyticus, genes within this cluster are involved in the synthesis of capsular polysaccharides (CPS) and play a role in the formation of biofilms (Chen et al, 2010). The cps cluster is known to be highly variable, and previous work has shown that recombination within this locus can be driven by chitin-induced transformation (Neiman et al, 2011). Five CPS proteins, unique to ST36, showed significant homology to putative virulence factors described in other Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…In this line it is worth noting that most antibiotics have been found to induce the SOS response in V. cholerae and increase the mutation frequency, even when present in subinhibitory concentrations (2), pointing to these as another source of mutability in this species. Moreover, all Vibrio species genomes sequenced so far carry the gene set required for natural transformation (55), and competence has be demonstrated for several of these (34,53,55); thus, the mechanisms described here could likely be applied to them. It would now be interesting to establish whether SOS is induced in the gut and, if so, to what extent it could induce the integrase.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, SOS also regulates some toxin-antitoxin (TA) systems (61); it can thus play a role in integron maintenance as there are 13 cassettes carrying TA systems in the V. cholerae SI (54). Several Vibrio species have been also demonstrated to be naturally competent (34,53,55), and it is very likely that many other Vibrio species, if not all, can also be transformed and, thus, that the SOS response induction we describe in V. cholerae is a common process for these species. It is very likely that the SOS response is highly conserved in all Vibrio species as LexA and LexA binding boxes are found upstream of the SOS regulon common genes (unpublished data), as well as upstream of the intIA gene in all the sequenced Vibrio genomes (13).…”
Section: Discussionmentioning
confidence: 99%
“…TfoX upregulates competence genes (119), which are involved in the production of a type IV pilus complex, four chitinases (including ChiA-1 and ChiA-2), and a chitoporin (127,128). The degradation of chitin (as discussed above) leads to increased concentrations of (GlcNAc) 2 , the smallest chitin polymer that induces competence in V. vulnificus (126) and in V. cholerae (127). Although GlcNAc is present in other sources, such as glycolipids and polysaccharides, the dimer (GlcNAc) 2 is only derived from chitin degradation.…”
Section: Chitin-induced Competencementioning
confidence: 99%
“…Successful chitinbased natural transformation of V. vulnificus (120), V. parahaemolyticus (121), and V. fischeri (122) have been reported and whole genome studies give evidence that HGT in V. cholerae is widespread in the natural environment (123). For example, studies have highlighted the importance of chitin-induced transformation and HGT in the conversion of nontoxigenic to toxigenic serogroups of V. cholerae (124, 125) and carbotype conversion of V. vulnificus (126), indicating that chitininduced transformation may play a large role in the acquisition of new genes in the environment.…”
Section: Chitin-induced Competencementioning
confidence: 99%